Spaceflight causes strain-dependent gene expression changes in the kidneys of mice - Rebecca H. Finch; Geraldine Vitry; Keith Siew; Stephen B. Walsh; Afshin Beheshti; Gary Hardiman; Willian A. da Silveira (npj Microgravity)
Abstract Incidence of kidney stones in astronauts is a major risk factor associated with long-term missions, caused by increased blood calcium levels due to bone demineralisation triggered by microgravity and space radiation. Transcriptomic changes have been observed in tissues during spaceflight, including the kidney. We analysed kidney transcriptome patterns in two different strains of mice flown on the International Space Station, C57BL/6J and BALB/c. Here we show a link between spaceflight and transcriptome patterns associated with dysregulation of lipid and extracellular matrix metabolism and altered transforming growth factor-beta signalling. A stronger response was seen in C57BL/6J mice than BALB/c. Genetic differences in hyaluronan metabolism between strains may confer protection against extracellular matrix remodelling through the downregulation of epithelial-mesenchymal transition. We intend for our findings to contribute to the development of new countermeasures against kidney disease in astronauts and people here on Earth.